Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Microbes Isolated from Ailanthus altissima Leaves Contribute to Samia cynthia’s Tolerance to the Toxic Quassinoid Diterpenoid - Jiaming Zhang; Juan Hua; Yangyang Wang; Jiayi Liu; Zhen Yang; Yanqun Liu; Shihong Luo (Journal of Chemical Ecology, 2026)

Effects of microenvironmental factors on water-insoluble precipitation induced by soybean urease - Chongda Duan; Jiaming Zhang; Yi Luo; Yanzi Sun; Jiaxing Liu; Xiang Lv (Journal of Environmental Chemical Engineering, 2026)

Tracking 3D desiccation crack evolution and permeability dynamics in expansive soil - Yun Peng; Jiaming Zhang; Yi Luo; Tianle Liu; Mingjian Hu; Shuai Liu (Bulletin of Engineering Geology and the Environment, 2026)

Gaδ+-H active sites-driven reverse water gas shift reaction with high CO selectivity - Zhenzhong Tao; Huaixiang Li; Dedong He; Zijun Huang; Jun Liang; Jiaming Dong; Xiaohua Cao; Yongming Luo (Chemical Engineering Journal, 2026)

Mechanical behavior of marine coral sand - coral clay mixtures reinforced with bionic honeycomb polymer grid: Experimental and artificial intelligence methods - Kaiwei Xu; Jiaqi Luo; Jiaming Zhao; Danda Shi; Zhiming Chao; Titi Sui (Ocean Engineering, 2026)

A comparative study of maturity, gas emissions, and microbial communities during kitchen waste, food waste, and food waste digestate composting - Xia Gao; Jiani Wang; Jiaming Li; Kaishu Luo; Xingshuai Yang; Guoxue Li; Yilin Kong; Jing Yuan (Journal of Environmental Chemical Engineering, 2026)

Urban Pluvial Flood Maximum Water Depth Prediction Using a Transformer-CNN Hybrid Deep Learning Model with Data Augmentation - Ziqi Liu; Dejun Zhu; Jiaming Luo; Danxun Li (Water Resources Management, 2026)

Synergistic effect in dual-site catalyst with silanol-stabilized Co2+-bonded Ni clusters for methane dry reforming - Zijun Huang; Dedong He; Han Xiao; Jun Liang; Jiaming Dong; Zhenzhong Tao; Xiaohua Cao; Dingkai Chen; Yongming Luo (Chemical Engineering Journal, 2026)

Low-cost, scalable fabrication of antibacterial asymmetric hydrogels inspired by mangrove systems for superior oil-water separation and salt-tolerant evaporation - Qidong Zha; Zuozhu Yin; Yingping Yang; Guoyan Yang; Jiaming Ni; Jilin Xu; Zhen Hong; Chan Xie; Yidan Luo; Mingshan Xue (Water Research, 2026)

MKAIS: A Hybrid Mamba–KAN Neural Network for Vessel Trajectory Prediction - Caiquan Xiong; Jiaming Li; Yuzhe Zhuang; Xinyun Wu; Mao Luo; Qi Wang (Journal of Marine Science and Engineering, 2025)
Vessel trajectory prediction (VTP) plays a critical role in maritime safety and intelligent navigation. Existing methods struggle to simultaneously capture long-term dependencies and nonlinear dynamic patterns in vessel movements. To address this challenge, we propose MKAIS, a novel trajectory prediction model that integrates the selective state space modeling capability of Mamba with the strong nonlinear representation power of Kolmogorov–Arnold Networks (KAN). Specifically, we design a feature-separated embedding strategy for AIS inputs (longitude, latitude, speed over ground, course over ground), followed by an MKAN module that jointly models global temporal dependencies and nonlinear dynamics. Experiments on the public ct_dma dataset demonstrate that MKAIS outperforms state-of-the-art baselines (LSTM, Transformer, TrAISformer, Mamba), achieving up to 16.65% improvement in the Haversine distance over 3 h prediction horizons. These results highlight the effectiveness and robustness of MKAIS for both short-term and long-term vessel trajectory prediction.

Transcriptomic and metabolomic analysis reveals the effect of hydrogen sulfide on delaying fruit ripening and color transition of white fleshed strawberry (Fragaria ananassa) - Miao Sun; Yue Wen; Xuanhuan Qiao; Tao Yang; Peng Zhao; Junhao Zhao; Jiaming Luo; Jialun Zhang; Zhipeng Zhu; Weijian Cai; Meng Xu; Li Yao; et al. (Postharvest Biology and Technology, 2025)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

ZnP-H2Im glass for flame retardant wood: In situ vitrification and synergistic mechanisms - Zhipeng Zhang; Jinrong He; Yuzhang Wu; Jiaming Luo; Wei Qu (Chemical Engineering Journal, 2025)

Parallel algorithm of watershed delineation by considering the topological relationship into information organisation - Fei Zhao; Liyang Xiong; Hongen Wang; Lanhua Luo; Jiaming Na; Sijin Li; Guoan Tang (Environmental Modelling & Software, 2025)

Impact of dynamic desiccation cracks on hydrological processes and stability in expansive clay slopes: A coupled dual-permeability modeling approach - Yi Luo; Jiaming Zhang; Chao-Sheng Tang; Guosheng Jiang; Thom Bogaard (Engineering Geology, 2025)

The links between Na/K ratios in eolian sands and mean annual precipitation in the deserts of arid region, northern China - Jiaqi Wang; Shipei Dong; Zhuolun Li; Jiaming Qu; Yuhan Kuai; Dianjia Tan; Jie Luo (CATENA, 2025)

Construction of biochar-zeolite composite for enhanced VOCs adsorption: Interfacial reinforcement and steam-driven synergistic regulation of pore formation and dealumination - Dingcheng Liang; Yajie Chang; Peipei Zhang; Yuan Liu; Chenhong Luo; Zhijun Zhang; Qiang Xie; Jiaming Liang; Kangzhou Wang; Xiao Yang; Qingping Chen; Zhucan Xie; et al. (Journal of Cleaner Production, 2025)

Efficient separation and recycling of waste wind turbine blades through in-situ generation of peroxyacetic acid - Xinyi Xu; Jiaming Liu; Jiachun Feng; Bin Chen; Shiwen Gong; Xueer Ouyang; Changxu Qin; Gang Luo; Shicheng Zhang (Resources, Conservation and Recycling, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Intumescent flame-retardant wood: In situ polymerization of ionic liquids and its mechanism - Jinrui Jiang; Yuzhang Wu; Jiaming Luo; Wei Qu (Chemical Engineering Journal, 2025)

The comparison of anticrystallization effects of cellulose derivatives with polyvinylpyrrolidone and poloxamer on andrographolide: In vitro and in vivo characterization - Xiaoyi Zhang; Peixia Luo; Jiaming Wang; Lei Yang; Zipei Pang; Shufeng Chen; Yi Zhou; Linghao Qin (Carbohydrate Polymers, 2025)

Enhancing the separation of iron and manganese from high-iron rhodochrosite through medium-low temperature calcination and leaching - Jiaming Chen; Jiancheng Shu; Huimin Yang; Sha Zhang; Jun Luo; Jing Wang; Hongyuan Zhao; Zongchen Wei; Yong Yang; Zongyu Deng; Mengjun Chen (Process Safety and Environmental Protection, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

Classification-enhanced LSTM model for predicting river water levels - Jiaming Luo; Dejun Zhu; Danxun Li (Journal of Hydrology, 2025)

Interaction between imidacloprid residues in maize rhizospheric soil and soil nematode community - Jiaming Zhang; Yue Wu; Jiayi Liu; Xinru Wang; Weijia Pang; Juan Hua; Shihong Luo (Pesticide Biochemistry and Physiology, 2025)

Selective complex leaching of Cu, Zn, and Cd from recycled copper smelting fly ash using NH3-NH4Cl system and kinetic analysis - Fan Lin; Tianya Lei; Jiancheng Shu; Mengjun Chen; Jibamu Duo; Xiangfei Zeng; Yunhui Han; Shaoqin Chen; Jiaming Chen; Weiping Huang; Jun Luo (Process Safety and Environmental Protection, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

Intergenerational differences and influencing factors of farmers’ terrace abandonment behavior: Based on a questionnaire survey of 2382 rural households in China - Jiaming Wen; Shilong Luo; Hualin Xie; Xiubin Li (Journal of Geographical Sciences, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Whole genome sequencing and analysis of Bacillus sp. TTMP2, a tetramethylpyrazine-producing bacterium - Shanling Gan; Lingru Ruan; Xinyi Xu; Lirong Luo; Yu Huo; Jiaming Jiang; Xiumin Zhang; Changhua Shang (Molecular Biology Reports, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Innovative approach to enhancing phosphogypsum mechanical properties and stabilizing/solidifying contaminants - Lina Xiao; Jiaming Zhang; Yi Luo; Xiaojian Qi; Javid Hussain; Guosheng Jiang (Sustainable Chemistry and Pharmacy, 2024)

Significantly enhancing high-temperature piezoelectric response and Tdr of BF-BT-based ceramics through multi-component optimization strategy - Huabin Yang; Jiaming Zhu; Xueting Wang; Qiuling Luo; Hua Tan; Haibo Zhang; Jiwen Xu; Qiaohong Chen (Chemical Engineering Journal, 2024)

Effects of dry-wet cycles on the mechanical properties of sandstone with unloading-induced damage - Gan Nan; Jiaming Zhang; Yi Luo; Xinlong Wang; Zhongyi Hu (Journal of Mountain Science, 2024)

Multiple synergistic antibacterial melamine-impregnated paper based on nano Ag-doped ZIF-8 - Jinrong He; Wei Qu; Yun Feng; Jinrui Jiang; Jiaming Luo; Yuzhang Wu; Limin Peng (Chemical Engineering Journal, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Effects of improper emergency mitigations on a large-scale landslide triggered by road excavation: A case study of the Fengping landslide, Hubei province, China - Yi Luo; Jiaming Zhang; Zhi Zhou; Guosheng Jiang; Modong Duan (Bulletin of Engineering Geology and the Environment, 2024)

Establishment of a gill cell line from yellowfin seabream ( Acanthopagrus latus ) for studying Amyloodinium ocellatum infection of fish - Zhicheng Li; Jingyu Zhuang; Jiaming Chen; Jizhen Cao; Qing Han; Zhi Luo; Baotun Wang; Hebing Wang; Anxing Li (Journal of Fish Diseases, 2024)
Amyloodinium ocellatum is among the most devastating protozoan parasites, causing huge economic losses in the mariculture industry. However, the pathogenesis of amyloodiniosis remains unknown, hindering the development of targeted anti‐parasitic drugs. The A. ocellatum in vitro model is an indispensable tool for investigating the pathogenic mechanism of amyloodiniosis at the cellular and molecular levels. The present work developed a new cell line, ALG, from the gill of yellowfin seabream ( Acanthopagrus latus ). The cell line was routinely cultured at 28°C in Dulbecco's modified Eagle medium (DMEM) supplemented with 15% fetal bovine serum (FBS). ALG cells were adherent and exhibited an epithelioid morphology; the cells were stably passed over 30 generations and successfully cryopreserved. The cell line derived from A. latus was identified based on partial sequence amplification and sequencing of cytochrome B ( Cyt b ). The ALG was seeded onto transwell inserts and found to be a platform for in vitro infection of A. ocellatum , with a 37.23 ± 5.75% infection rate. Furthermore, scanning electron microscopy (SEM) revealed that A. ocellatum parasitizes cell monolayers via rhizoids. A. ocellatum infection increased the expression of apoptosis and inflammation‐related genes, including caspase 3 ( Casp 3 ), interleukin 1 ( IL‐1 ), interleukin 10 ( IL‐10 ), tumour necrosis factor‐alpha ( TNF‐α ), in vivo or in vitro. These results demonstrated that the in vitro gill cell monolayer successfully recapitulated in vivo A. latus host responses to A. ocellatum infection. The ALG cell line holds great promise as a valuable tool for investigating parasite–host interactions in vitro.

Aggregation, retention and transport of γ-MnO2 nanoparticles in water-saturated porous media: Impact on the immobility of thallium - Jiaming Luo; Dafeng Cai; Lezhang Wei; Hang Shi; Yu Liu; Haiqi Yan; Dinggui Luo; Tangfu Xiao; Xuexia Huang; Qihang Wu (Environmental Pollution, 2024)

Thermal inactivation kinetics of Listeria monocytogenes in milk under isothermal and dynamic conditions - Xiang Wang; Jiaming Zheng; Linyin Luo; Yi Hong; Xiaofeng Li; Yuqi Zhu; Yufan Wu; Li Bai (Food Research International, 2024)

Heterologous expression of protein-glutaminase in Escherichia coli Nissle 1917 for improved flavor properties of soy protein and its implications on high-moisture extrudates - Jiaming Li; Xinwen Zhang; Shijun Luo; Xinhong Wu; Guoqiang Zhang; Jianghua Li; Xiao Liu (Food Bioscience, 2024)

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

Revealing the spatio-temporal characteristics and impact mechanism of carbon emission in China's urban agglomerations - Ziyi Wang; Jingxiang Zhang; Pingjia Luo; Dongqi Sun; Jiaming Li (Urban Climate, 2023)

Thermal-and-mechanochemical recycling of waste polypropylene into maleated-epoxided degradation products as warm-mix asphalt modifier: Performance improvement and production mechanism analysis - Xiong Xu; Yaming Chu; Yi Luo; Yuhao Peng; Nannan Yang; Jiaming Yan; Xuyong Chen; Fuliao Zou; Anand Sreeram (Journal of Cleaner Production, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Self-repairing thermal energy storage gels demonstrating superior thermophysical properties and wearability towards personal thermal management in static and dynamic modes - Yingying Luo; Hongjiao Wu; Junpeng Qiao; Jiaming Zhang; Kai Liu; Liqing Zou; Ying Chen; Pengcheng Lin (Chemical Engineering Journal, 2023)

Direct start-up of aerobic granular sludge system with dewatered sludge granular particles as inoculant - Zhuo Sun; Jiaming Zhang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Guoyou Nong; Mengqi Luo; Jue Wang (Journal of Environmental Management, 2023)

Energy management of the grid-connected residential photovoltaic-battery system using model predictive control coupled with dynamic programming - Bin Zou; Jinqing Peng; Rongxin Yin; Zhengyi Luo; Jiaming Song; Tao Ma; Sihui Li; Hongxing Yang (Energy and Buildings, 2023)

Mechanisms of PiT2-loop7 Missense Mutations Induced Pi Dyshomeostasis - Hao Sun; Xuan Xu; Junyu Luo; Tingbin Ma; Jiaming Cui; Mugen Liu; Bo Xiong; Shujia Zhu; Jing-Yu Liu (Neuroscience Bulletin, 2023)

Tilt deformation and instability of the slope for predicting rainfall-induced landslide - Handong Liu; Jing-jing Liu; Jiaxing Chen; Jiaming Luo; Wei Guo (Arabian Journal of Geosciences, 2022)

Failure mechanism of a slow-moving landslide on September 27, 2020, in Chang Nong Village, Guangxi, China - Jiaming Zhang; Zhi Zhou; Feng Lin; Qinggang Yang; Yi Luo (Landslides, 2021)

Research on the rainfall-induced regional slope failures along the Yangtze River of Anhui, China - Jiaming Zhang; Yi Luo; Zhi Zhou; Chikhotkin Victor; Modong Duan (Landslides, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Large-Scale Test Model of the Progressive Deformation and Failure of Cracked Soil Slopes - Zhi Zhou; Jiaming Zhang; Fulong Ning; Yi Luo; Lily Chong; Kuangbiao Sun (Journal of Earth Science, 2020)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)